Application of a non-invasive technique for estimating clutch size in the Caribbean spiny lobster Panulirus argus (Latreille, 1804). Issue 1 (2nd December 2017) - Gnanalingam, Gaya; Butler, Mark J
Abstract: We investigated the use of a non-invasive method of fecundity estimation for the Caribbean spiny lobster, Panulirus argus (Latreille, 1804 ), using a method previously described for the American clawed lobster, Homarus americanus (Milne Edwards, 1837 ). This method only requires the removal of a small subsample of eggs from each individual as compared to traditional gravimetric methods that strip females of their entire clutch. Comparisons of the non-invasive method with traditional estimates resulted in egg count estimates that differed by a mean of 0.003% but a mean absolute value of 42%. Our results demonstrate the utility of this rapid, inexpensive, and non-destructive method for estimating clutch size for a highly fecund species. Differences between estimates produced using this new method and the traditional gravimetric method are substantial, and therefore it's accuracy in relation to the traditional gravimetric method remains unknown.